Post-Stroke Administration of L-4F Promotes Neurovascular and White Matter Remodeling in Type-2 Diabetic Stroke Mice - Zhou, Min; Li, Rongwen; Venkat, Poornima; Qian, Yu; Chopp, Michael; Zacharek, Alex; Landschoot-Ward, Julie; Powell, Brianna; Jiang, Quan; Cui, Xu (Frontiers in Neurology, 2022)
Patients with type 2 diabetes mellitus (T2DM) exhibit a distinct and high risk of ischemic stroke with worse post-stroke neurovascular and white matter (WM) prognosis than the non-diabetic population. In the central nervous system, the ATP-binding cassette transporter member A 1 (ABCA1), a reverse cholesterol transporter that efflux cellular cholesterol, plays important role in high-density lipoprotein (HDL) biogenesis and in maintaining neurovascular stability and WM integrity. Our previous study shows that L-4F, an economical apolipoprotein A member I (ApoA-I) mimetic peptide, has neuroprotective effects via alleviating neurovascular and WM impairments in the brain of db/db-T2DM stroke mice. To further investigate whether L-4F has neurorestorative benefits in the ischemic brain after stroke in T2DM and elucidate the underlying molecular mechanisms, we subjected middle-aged, brain-ABCA1 deficient (ABCA1-B/-B) and ABCA1-floxed (ABCA1fl/fl) T2DM control mice to distal middle cerebral artery occlusion. L-4F (16mg/kg, subcutaneous) treatment was initiated 24 hours after stroke and administered once daily for 21 days. Treatment of T2DM-stroke with L-4F improved neurological functional outcome, and decreased hemorrhage, mortality, and BBB leakage identified by decreased albumin infiltration and increased tight-junction and astrocyte end-feet densities, increased cerebral arteriole diameter and smooth muscle cell number, and increased WM density and oligodendrogenesis in the ischemic brain in both ABCA1-B/-B and ABCA1fl/fl T2DM-stroke mice compared with vehicle-control mice, respectively (p<0.05, n=9 or 21/group). L-4F treatment reduced macrophage infiltration and neuroinflammation identified by decreases in ED-1, monocyte chemoattractant protein-1 (MCP-1) and toll-like receptor 4 (TLR4) expression, and increases in anti-inflammatory factor Insulin-like growth factor 1 (IGF-1) and its receptor IGF-1 receptor β (IGF-1Rβ) in the ischemic brain (p<0.05, n=6/group). These results suggest that post-stroke administration of L-4F may provide a restorative strategy for T2DM-stroke by promoting neurovascular and WM remodeling. Reducing neuroinflammation in the injured brain may contribute at least partially to the restorative effects of L-4F independent of the ABCA1 signaling pathway.